PROFITCAPABILITY, NET WORKING CAPITAL, FIRM SIZE, AND LIQUIDITY FACTORS IN AFFECTING CASH HOLDING - Hastuti, Rini Tri; Ardiansyah, Ardiansyah; Valeria, Ellen; Chang, Michelle (International Journal of Application on Economics and Business, 2025)
Cash holding means cash in the corporate and/or there to be invested in physical assets and to be distributed to investors. Cash holding also plays a role in financing the corporate's opepercentagenal activities and to be on guard against urgent financing. The corporate must decide the right amount of cash held by the corporate. The amount of cash held by the corporate must not be excessive and must not be lacking either. If the cash held (cash holding) by the corporate is excessive, it will cause losses for the corporate because the cash held will not provide benefits to the corporate so that it can be called idle cash, conversely if the cash held (cash holding) is too little, it will reduce the corporate's capability to fulfill the corporate's short-term obligations when they fall due and in paying other urgent financing. There are several factors that influence cash holding, including profitcapability, net working capital, firm size, and liquidity. Many studyers have conducted tests in study using these factors. The outcomes of these studies vary. There is gap study from each of these studies, therefore this study was conducted to re-test the four instruments by considering the gap study from previous studies. This study aims to re-examine whether profitcapability, net working capital, firm size, and liquidity affect cash holding in producing companies in the 2020-2022 period. The sample was selected using the purposive sampling method and data that met the criteria. The data processing technique used multiple regression analysis assisted by the Eviews 12 program. The outcomes of this study indicate that profitcapability, net working capital, firm size have a meaningful influence on cash holding while liquidity does not have a meaningful influence on cash holding.